9+3(z-3)=2z+3

Simple and best practice solution for 9+3(z-3)=2z+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+3(z-3)=2z+3 equation:


Simplifying
9 + 3(z + -3) = 2z + 3

Reorder the terms:
9 + 3(-3 + z) = 2z + 3
9 + (-3 * 3 + z * 3) = 2z + 3
9 + (-9 + 3z) = 2z + 3

Combine like terms: 9 + -9 = 0
0 + 3z = 2z + 3
3z = 2z + 3

Reorder the terms:
3z = 3 + 2z

Solving
3z = 3 + 2z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-2z' to each side of the equation.
3z + -2z = 3 + 2z + -2z

Combine like terms: 3z + -2z = 1z
1z = 3 + 2z + -2z

Combine like terms: 2z + -2z = 0
1z = 3 + 0
1z = 3

Divide each side by '1'.
z = 3

Simplifying
z = 3

See similar equations:

| 1.9n-48.4=3n | | 5.2+y=7.9 | | x^2+y^2=44 | | 4(3x)-8x/2=216 | | 2x+5x=42 | | (8/7)(8/7)= | | 27+t=-31 | | -83+5x=-2x+78 | | 8/7*8/7= | | 1-2x+2x=13 | | 7-7m=-5m+11 | | r-4x=10 | | (7x5)/5 | | S+42=18 | | 4x+6+3x+1=8x-2 | | b-3y=12 | | 11x-21=12+10x | | 1+3(4x-4)=11(2x-1) | | 3x/5=2.1 | | n+6=1/12 | | (8/7)^-2= | | 3(2x-1)+5=5(x-1) | | 9+a=0 | | 6x-2+8x=3x+4-5x | | (8/7)6-2= | | 12x-11=22x-11 | | -8x+5+3x=-10x-25 | | 5g(-3)=3x+1 | | 6.6-1/3 | | 1/2y-2=1/5 | | 6(x+4)-6x=1(x-9) | | 7x-(6x+4)=3x-50 |

Equations solver categories